2006
DOI: 10.1111/j.1479-8425.2006.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the reduced version of the Morningness-Eveningness Questionnaire

Abstract: The aim of the present work was to validate the reduced version of the Morningness-Eveningness Questionnaire (MEQr) using circadian motor activity as external criterion. The MEQr was administered to a sample of 130 university students, 42 males and 88 females. All the students wore an actigraph (AMI 32K) on the non-dominant wrist for three consecutive nights and days. Acrophase was computed using cosinor analysis. The circadian motor activity of evening types presented a significant phase delay versus intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 3 publications
4
114
0
Order By: Relevance
“…The MEQr has been shown to successfully identify human circadian typology in both experimental and applied research 6. Three questions establish the preferred morning wake-up time, evening bedtime and the hour of the day when personal efficiency is maximal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MEQr has been shown to successfully identify human circadian typology in both experimental and applied research 6. Three questions establish the preferred morning wake-up time, evening bedtime and the hour of the day when personal efficiency is maximal.…”
Section: Methodsmentioning
confidence: 99%
“…The MEQr originally established five behavioral categories: definitively morning-type (score, 22-25), moderately morning-type (score, 18-21), neither-type (score, 12-17), moderately evening-type (score, 8-11) and definitively evening-type (score, 4-7). In the present study, we adopted the simpler classification used by Taillard and colleagues and other researchers: morning-type (M-type; score, 18-25), neither-type (N-type; score, 12-17) and evening-type (E-type; score, 4-11) 5689…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus rMEQ-5 offers an easy, reliable equivalent to the rMEQ scale, measure of individuals' chronotype. Previous studies (Natale et al, 2006;Tonetti et al, 2011) have suggested that the midpoint of sleep, calculated considering the hourly preference for getting up or go to sleep (rMEQ items' 1 and 3) may offer a reliable measure of the circadian typology. Although that measure is a more indirect self-assessment measure than the one offered by rMEQ-5 item we interpret those results as also corroborating our argument that chronotype is a conscious dimension able of selfassessment.…”
Section: Discussionmentioning
confidence: 99%
“…Following comments in the literature concerning the length and the practicality for researchers of the relatively long nineteen-item MEQ (e.g., Natale, Esposito, Martoni, & Fabbi et al, 2006), we explored a reduced, more practical scale. Therefore, an additional purpose of Study 2 was to employ a reduced version of Horne and Ostberg's (1976) questionnaire (MEQr), shown to be psychometrically sound and easily implemented in marketing studies.…”
Section: Studymentioning
confidence: 99%